Leaving teaching: lack of resilience or sign of agency?. Issue 8 (17th November 2017) - Smith, Kari; Ulvik, Marit
Abstract: Alarming numbers of teacher attrition are reported in many countries, including in Norway. Whereas most of the research tells about personal and professional negative experiences which have a harmful impact on teachers' resilience, a different approach is taken in the current paper. Four cases of leavers are purposefully selected because they represent qualified teachers who left the profession, not because they were unhappy with the job or had negative experiences, but because they needed more space and autonomy than they had as teachers. The findings show that their motives for teaching were mainly intrinsic, they were successful teachers, however, they became restless and left their secure jobs to start afresh, and they succeeded. We suggest that it is time to examine the strength of the leavers and accept that teaching is not a lifelong 'call' for some of its best people. It is time to seek new ways to revive the profession.